THE USE OF BLOCKCHAIN TECHNOLOGY IN IMPROVING THE PROCESS OF INFORMATION EXCHANGE IN THE TAX FIELD - Uchqunova Dilshoda Numonjon qizi ,; Xolmatov Numonjon Meliboyevich , (Journal of new century innovations, 2022)
Abstract: The use of blockchain technology in the tax system is quite new and has not been studied so far in the context of developing nations. The paper explores how blockchain technology can be applied to the indirect tax system, specifically for exchanging electronic information. In addition, the tax invoices serial numbers transactions are tracked and analyzed.